2020
DOI: 10.1016/j.jsams.2020.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Bowling loads and injury risk in male first class county cricket: Is ‘differential load’ an alternative to the acute-to-chronic workload ratio?

Abstract: Bowling loads and injury risk in male first class county cricket: Is 'differential load' an alternative to the acute-to-chronic workload ratio? Abstract Objectives: Methodological concerns relating to acute-to-chronic workload ratios (ACWR) have been raised. This study aimed to assess the relationship between an alternative predictor variable named 'differential load', representing the smoothed week-to-week rate change in load, and injury risk in first class county cricket (FCCC) fast bowlers. Design: Prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…This came out as one of the top factors influencing player monitoring in the survey, illustrated by one practitioner in the interviews who admitted they come up with different theories each year to developing and monitoring workloads. To illustrate, bowling workload has been shown to be an important factor within cricket, 35 , 10 and featured heavily in both survey and interview responses in this study. Participants described widespread use of ACWR 8 , 29 to minimise injury risk, 30 however, there is poor evidence to support ACWR as a risk factor for injury, 3132 and it has been criticised for failing to account for the decaying nature of fitness and fatigue effects over time.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…This came out as one of the top factors influencing player monitoring in the survey, illustrated by one practitioner in the interviews who admitted they come up with different theories each year to developing and monitoring workloads. To illustrate, bowling workload has been shown to be an important factor within cricket, 35 , 10 and featured heavily in both survey and interview responses in this study. Participants described widespread use of ACWR 8 , 29 to minimise injury risk, 30 however, there is poor evidence to support ACWR as a risk factor for injury, 3132 and it has been criticised for failing to account for the decaying nature of fitness and fatigue effects over time.…”
Section: Discussionmentioning
confidence: 78%
“…33 With the continued debate on suitable calculation methods the use of ACWR should continue to be tested with further investigation warranted into what acute and chronic time periods might be more appropriate for use in cricket. 5 Given the common use of bowling overs, alternatives for monitoring workloads, such as ‘exponentially weighted moving averages’ (EWMA), 34 should also be explored in future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only two studies [34,42] included in this review used the EWMA model and suggested that the EWMA model was a better alternative to rolling averages for assessing injury risk. Some studies show that while both models demonstrate significant associations between ACWR and injury risk [49][50][51], rolling ACWRs may underestimate the injury risk at higher ACWR ranges [49,50,52,53], while others suggest that there are no differences between the rolling averages and the EWMA methods [51]. Studies included in this review support both methods, but when directly compared, the EWMA model shows greater sensitivity.…”
Section: How To Best Calculate the Acwr? The Decision Requires Contextmentioning
confidence: 79%
“…We can measure the ratio of acute:chronic load in internal load variables (Example: RPE, TRIMP, among others), as well as in external load variables (total distance, distances travelled to sprint, distances travelled at high intensity, number of accelerations / decelerations, etc. ), recommending its analysis in those variables that have a high relationship with the injury index (accelerations and decelerations of high intensity, high speeds, sprint speed, RPE, heart rate> 90%, among others) (Gabbett et al , 2014;Sekiguchi et al, 2018;Tysoe et al, 2020). Its use will give us information about the state of fitness or fatigue of the athlete and can be used as a useful tool for the prediction of sports injuries (Blanch and Gabbett, 2016).…”
Section: Discussionmentioning
confidence: 99%